Celastrol inhibits store operated calcium entry and suppresses psoriasis - Yuan, Xiaoman; Tang, Bin; Chen, Yilan; Zhou, Lijuan; Deng, Jingwen; Han, Lin; Zhai, Yonggong; Zhou, Yandong; Gill, Donald L.; Lu, Chuanjian; Wang, Youjun (Frontiers in Pharmacology, 2023)
Psoriasis is an inflammatory autoimmune skin disease that is hard to cure and prone to relapse. Currently available global immunosuppressive agents for psoriasis may cause severe side effects, thus it is crucial to identify new therapeutic reagents and druggable signaling pathways for psoriasis. Store operated calcium (Ca2+) entry (SOCE), mediated by STIM1 and Orai1, is crucial for the function of keratinocytes and immune cells, the two major players in psoriasis. Here we showed that a natural compound celastrol is a novel SOCE inhibitor, and it ameliorated the skin lesion and reduced PASI scores in imiquimod-induced psoriasis-like mice. Celastrol dose- and time-dependently inhibited SOCE in HEK cells and HaCat cells, a keratinocyte cell line. Mechanistically, celastrol inhibited SOCE via its actions both on STIM1 and Orai1. It inhibited Ca2+ entry through constitutively-active Orai1 mutants independent of STIM1. Rather than blocking the conformational switch and oligomerization of STIM1 during SOCE activation, celastrol diminished the transition from oligomerized STIM1 into aggregates, thus locking STIM1 in a partially active state. As a result, it abolished the functional coupling between STIM1 and Orai1, diminishing SOCE signals. Overall, our findings identified a new SOCE inhibitor celastrol that suppresses psoriasis, suggesting that SOCE pathway may serve as a new druggable target for treating psoriasis.